2007
DOI: 10.1093/jac/dkm168
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and widespread dissemination of multidrug-resistant blaCMY-2Salmonella Typhimurium in Mexico

Abstract: The rapid and widespread dissemination of MDR blaCMY-2 Salmonella Typhimurium in Mexico calls for urgent interventions to contain this potentially fatal pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 9 publications
4
46
0
1
Order By: Relevance
“…Plasmid-mediated AmpC resistance has recently been reported in clinical isolates of the Enterobacteriaceae worldwide (6,7,9,22,23,(30)(31)(32). Few population-based studies have reported on the frequency or clinical impact of these isolates, and very little is known about the associated epidemiology in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid-mediated AmpC resistance has recently been reported in clinical isolates of the Enterobacteriaceae worldwide (6,7,9,22,23,(30)(31)(32). Few population-based studies have reported on the frequency or clinical impact of these isolates, and very little is known about the associated epidemiology in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance in our S. Typhimurium isolates is the most pressing concern. bla CMY-2 S. Typhimurium is now a major public health problem in Yucatan, where its prevalence in- and where it has caused fatal infections in young infants (18). The higher rate of ESC resistance in ill children with S. Typhimurium infection than in asymptomatic children has 2 possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…In samples of pig origin, the percentages of AmpCcarrying Salmonella or E. coli isolates ranged from 2.4 to 23% in Canada, Taiwan and México (Kozak et al, 2009;Yan et al, 2004;Zaidi et al, 2007).…”
Section: Cattle Originmentioning
confidence: 99%